Composition, buoyancy regulation and fate of ice algal aggregates in the Central Arctic Ocean. - Mar Fernández-Méndez; Frank Wenzhöfer; Ilka Peeken; Heidi L Sørensen; Ronnie N Glud; Antje Boetius (PLoS ONE, 2014)
Sea-ice diatoms are known to accumulate in large aggregates in and under sea ice and in melt ponds. There is recent evidence from the Arctic that such aggregates can contribute substantially to particle export when sinking from the ice. The role and regulation of microbial aggregation in the highly seasonal, nutrient- and light-limited Arctic sea-ice ecosystem is not well understood. To elucidate the mechanisms controlling the formation and export of algal aggregates from sea ice, we investigated samples taken in late summer 2011 and 2012, during two cruises to the Eurasian Basin of the Central Arctic Ocean. Spherical aggregates densely packed with pennate diatoms, as well as filamentous aggregates formed by Melosira arctica showed sign of different stages of degradation and physiological stoichiometries, with carbon to chlorophyll a ratios ranging from 110 to 66700, and carbon to nitrogen molar ratios of 8-35 and 9-40, respectively. Sub-ice algal aggregate densities ranged between 1 and 17 aggregates m(-2), maintaining an estimated net primary production of 0.4-40 mg C m(-2) d(-1), and accounted for 3-80% of total phototrophic biomass and up to 94% of local net primary production. A potential factor controlling the buoyancy of the aggregates was light intensity, regulating photosynthetic oxygen production and the amount of gas bubbles trapped within the mucous matrix, even at low ambient nutrient concentrations. Our data-set was used to evaluate the distribution and importance of Arctic algal aggregates as carbon source for pelagic and benthic communities.